Effects of Excess Cr3+ on Trace Element Contents in the Brain and Serum in Chicken - Liu, Yanhan; Hao, Pan; Zhang, Xiao; Zhao, Xiaona; Liu, Yongxia; Liu, Jianzhu (Biological trace element research, 2017)
This study aimed to investigate the effects of chromic chloride (CrCl 3 ) on Ca, Mg, Mn, Fe, Cu, and Zn contents in the brain and serum of chicken. Seventy-two chickens were randomly divided into four groups and treated with different doses of CrCl 3 via drinking water: 0, 1/8, 1/4, and 1/2 LD 50 for 42 days. The contents of the elements were evaluated through inductively coupled plasma mass spectrometry. Results showed that Cr contents in the brain and serum were higher than those in the control groups, although no significant dose-dependent changes ( P > 0.05 ) in brain of the Cr-treated groups were observed at 42 days. As exposure time was prolonged and CrCl 3 dosage was increased, Ca contents increased ( P < 0.05 ). Mg and Cu contents in serum decreased; by contrast, Mg and Cu contents initially increased and then decreased in the brain. Fe and Zn contents in the serum increased; conversely, Fe and Zn contents in the brain decreased. CrCl 3 exposure did not significantly affect Mn contents at 14 or 28 days, but significantly decreased ( P < 0.05 ) at 42 days. Therefore, excess Cr 3+ intake can disrupt absorption and deposition of other trace elements in the brain and serum; the blood–brain barrier may prevent the accumulation of these elements in the brain exposed to CrCl 3 .